Association Between Socio-Cultural Factors and HIV And AIDS - Karki, Tej Bahadur (Journal of Advanced Academic Research, 2017)
Background: society is a web of relationship and cultural is manmade. Social change depends on the socio-cultural norms and values. With changing of society, prevalence of HIV and AIDS came in existence from 1988 in Nepal and brought the disturbance on social harmony. This study investigated the roles of socio-cultural factors increasing the risk of HIV and AIDS in Nepalese context. Methods: study was non-experimental cross sectional. In total 404 respondents were randomly selected from the workers of long route transport, brick factory, and garment factory and health sectors. The study was conducted from Oct 2012 to Mar 2013 in Kathmandu valley. Result: There was association found between stigma (p=.033), human trafficking (p=.000), trust on sex partners (p=.001), gender based violence (p=.000), early marriage (p=.000), gender inequality (p=.000) and polygamy (p=.002) and HIV and AIDS. 56.7%, 93.6%, 77.0% and 94.3% respondents agreed on association between the stigma and discrimination, human trafficking, trust on sex partners and polygamy respectively with HIV and AIDS. Similarly, 52% respondents were found disagree on association between early marriage with risk of HIV transmission. Majority of respondents are not sure to say the association of genders based violence (36.7%) and gender inequality (36.1%) with risk of HIV and AIDS. Conclusion: Significant association found between the socio-cultural factors (such stigma and discrimination, human trafficking, trust on sex partners, gender based violence, early marriage system, gender inequality and polygamy) and HIV and AIDS.